Continuous Electrocoagulation Process for the Treatment of High Colloidal Clay in Coal Mine Water using Lab Scale Baffle Channel Reactor - Muhammad Sonny Abfertiawan; Althaf Gavin Azarya; Syarif Makki Zamani; Mindriany Syafila; Marisa Handajani (School of Postgraduate Studies, Diponegoro Univer, 2026)
The electrocoagulation (EC) process has been extensively studied in recent years for the removal of various contaminants present in wastewater, such as metals, organic materials, dyes, oils, pharmaceutical compounds, and other emerging pollutants. In the mining industry, EC development continues to be conducted for the removal of contaminants in mine water, which is characterized by high acidity and suspended solids. This study aims to develop EC for the removal of suspended solids caused by the presence of colloidal clay from overburden during mining activities. EC was operated using a lab-scale baffle channel reactor with a volume of 15 liters in continuous mode, utilizing monopolar iron and aluminum electrode pairs. To obtain optimal performance, the study focused on the influence of three parameters affecting EC: current density (2 A, 4 A, and 6 A), electrode type (iron and aluminum), and residence time in the reactor (15 minutes, 30 minutes, and 45 minutes, equivalent to flow rates of 0.3, 0.5, and 1 LPM). The results demonstrated that the highest suspended solids removal of 99.66% occurred in the iron electrode reactor with a current strength of 6 amperes and an HRT of 45 minutes or a flow rate of 0.3 liters per minute. The reactor with aluminum electrodes achieved a removal percentage of 99.11% with a current strength of 6 amperes and an HRT of 15 minutes or a flow rate of 1 liter per minute. This research represents an advanced stage of batch operation in efforts to develop field-scale EC for the treatment of mine water with high colloidal clay content.